Correlation Analysis between GDM and Gut Microbial Composition in Late Pregnancy. (10th February 2021) - Li, Genxia; Yin, Pan; Chu, Shuhui; Gao, Wanli; Cui, Shihong; Guo, Shuhua; Xu, Yajuan; Yuan, Enwu; Zhu, Texuan; You, Jie; Zhang, Junya; Yang, Manman
Abstract : The prevalence of GDM is very high worldwide. The specific pathogenesis of GDM is currently not very clear. Recent research suggests that changes in the intestinal flora during pregnancy play a key role in it. Therefore, this study is aimed at exploring the characteristics of the intestinal flora of patients with gestational diabetes in the third trimester of pregnancy and at finding the intestinal flora with significant differences in healthy pregnant women to provide a basis for future clinical attempts of using intestinal microecological agents to treat gestational diabetes mellitus (GDM). We sequenced the V3-V4 regions of the 16S ribosomal ribonucleic acid (rRNA) gene from stool samples of 52 singleton pregnant women at >28 weeks of gestation. Our results showed that there were significant differences between the NOR group vs. GDM group and the G group vs. LG group among Bacteroides, Firmicutes, and Firmicutes/Bacteroides. At the species level, there were significant differences in the abundance of eight species in the NOR and GDM groups. Among them, the relative abundance of Clostridium_spiroforme, Eubacterium_dolichum, and Ruminococcus_gnavus was positively correlated with FBG, and Pyramidobacter_piscolens was negatively correlated with FBG, whereas there were significant differences in the abundance of five species in the G and LG groups. Functional analysis showed that there were differences in the biosynthesis and metabolism of polysaccharides, digestive system, classification, and degradation of the intestinal microbes between the NOR and GDM groups and between the G and LG groups. These results indicated that the gut microbes between GDM patients in the third trimester of pregnancy and healthy controls had essential characteristic changes and might be involved in the regulation of patients' blood glucose levels.